Establishing a Smart Hospital Environment using RFID Technology - Acharya, Rathnakar; Nagarajan, S (Gyan Management Journal, 2008)
This is the information age. Information plays a very vital pivotal and critical role in today's society. Human dependenc on information for daily living working and relaxing is growing. Every human activity, intention task and assignment is intertwined with availability, timeliness and corr ctness of information. Nowadays a tremendou amoun of information is being generated, by humans, machines tool and instruments. Simultaneously there is a bewildering array of nabling technologies and infrastructures for automatic capturing creating, effi ienl proc ssing, secured storing, and transmi ting data. Also ther ar prov n algorithms and intuitiv interfac for precisely mining and extracting intelligence out of th burgeoning information h ap. In the recent pa t, location information ha become a very crucial and fascinating component in realizing a number of exciting and real-tim servic s for per onal as well as professional convenience and comfort.
Keywords: Hospital; RFID Technology